The Uncertain Path Toward College: How Intersectionality Shaped the Experiences of Latinas Enrolled at a Hispanic-Serving Institution - Ruth M. López; Maria L. Honey; Stephanie Rendon; Stephanie Pérez-Gill (SAGE Publishing, 2022)
This is a longitudinal qualitative study of Latina college students who were members of a Latina mentoring program at a 4-year Hispanic-Serving Institution (HSI) in Texas, where they made up the largest student population since 2013. Guided by Chicana feminist epistemology and intersectionality, we discuss educational experiences students had during high school as they considered their college path, when enrolling in an HSI, and during college. We explore the following research question: How did intersectional experiences shape the educational trajectory of Latina undergraduates enrolled at an HSI? We identify how multiple forms of oppression and social identities shaped the high school experiences of Latinas and learned how they found belonging at an HSI by finding spaces and individuals who validated their intersectionality. Through this study, we demonstrate why Latina student intersectionality-not only while in college but prior to enrolling as well-is important for researchers and educational leaders to consider.